Peningkatan Kompetensi Menulis Karya Ilmiah bagi Guru MGMP Bahasa Inggris SMA Se-Kabupaten Nganjuk melalui Pelatihan Publikasi dengan TEFLIN Journal (Teaching English as a Foreign Language in Indonesia) - Junining, Esti; Khasanah, Ismatul; Muttaqin, Syariful (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2023)
Abstract Teacher competency development in Indonesia is a gradual and progressive task that is intended to increase teachers’ professionalism. In accordance with Permenpan RB Number 16 of 2009 concerning Teacher Functional Positions and Credit Points, Junior Superintendent IIIa who wishes to advance to First Class Junior Superintendent IIIb must obtain 3 points for self-development and teachers who wish to advance from First Class Junior Superintendent IIIb to Superintendent IIIc must obtain 4 points for professional development from scientific publications or innovative works. The writing of scholarly articles by teachers is fostered by Law Number 18 of 2007, which has made it a requirement, one of the parameters used to evaluate in-service teacher certification portfolio, and one of the forms of activity or professional development work that is highly respected. Regrettably, teachers encounter some obstacles in producing and publishing scholarly articles so errors are regularly made while submitting manuscripts to the predatory journal.